Absorption of foreign knowledge: Firms' benefits of employing immigrants - Jürgen Bitzer; Erkan Gören; Sanne Hiller (University of Oldenburg, Department of Economics, 2015)
This paper explores the question of how immigrant employees affect a firm's capacity to absorb foreign knowledge. Using matched employer-employee data from Denmark for the years 1996 to 2009, we are able to show that non-Danish employees from technologically advanced countries contribute significantly to a firm's total factor productivity (TFP) through their ability to access foreign knowledge. The empirical results suggest that the impact increases if the immigrants come from technologically advanced countries, are highly educated, and work in high-skilled positions.
Keywords: D20; J82; L20; O30; 330; R&D Spillovers; Absorptive Capacity; Firm-Level Analysis; Foreign Workers; Immigrants